Do shared bicycles promote residents’ consumption? - Yongli Chen; Xi Zhu; Jing Li; Yuge Bai (China Economic Quarterly International)
Using China Family Panel Studies (CFPS) data from 2010 to 2018, this paper employs a staggered difference-in-differences (DID) approach to unveil that the entry of bike-sharing significantly boosts per capita household expenditure by 3.9%–6.8%, along with an increase of 3.8%–4.9% in dining-out expenses. The analysis of mechanisms indicates that bike-sharing reduces the time cost per unit of consumption by alleviating traffic congestion, increases leisure time by reducing commute duration, and enhances net income by lowering rental expenses without affecting wage. Our findings provide evidence for the impact of the sharing economy on consumption and its mechanisms.